Διερευνώντας την επίδραση των βίντεο 360ο στην εμπειρία χρήστη, στα κίνητρα μάθησης και στα μαθησιακά κέρδη των χρηστών - Πύρκα, Κυριακή (My University, 2024)
This thesis focuses on investigating the impact of interface (computer screen, virtual reality glasses) on user experience, learning motivation, and learning outcomes of university students, when watching 360-degree educational videos. Recruiting a sample of 179 students from the Cyprus University of Technology, who were randomly divided in two conditions according to the interface they used, differences were examined between watching a 360-degree educational video on a desktop computer (flat screen) or with virtual reality glasses. Data collection was conducted through questionnaires assessing user experience and learning motivation, as well as pre- and post-intervention comprehension tests to evaluate students’ learning gains. The results showed that there were no significant differences in learning outcomes between the two groups. However, users of virtual reality glasses reported higher levels of motivation, in terms of relevance, compared to computer users, indicating that the content seemed more interesting and more important to them. Collectively, the findings of this thesis suggest that, while educational interfaces do not directly affect learning outcomes, virtual reality glasses can be used as a learning motivator and the quality of the experience can enhance user engagement and satisfaction, indirectly contributing to the learning process.
Keywords: 360-degree videos; Learning motivation; User experience; Learning outcomes; Interface; Βίντεο 360 μοιρών; Μαθησιακά κίνητρα; Εμπειρία χρήστη; Μαθησιακά κέρδη; Διεπαφή